The Calgary Stampede Through a Cultural Studies Perspective: A Teaching Project. (February 2016) - Rosenthal, Caroline; Schäfer, Stefanie
This essay presents the conception, outline, and results of a cultural and literary studies graduate course held at the Friedrich Schiller University in Jena and at the Calgary Stampede in 2013. Students of English and American Studies from Germany developed multimedia projects about "Western" culture, and the Stampede as a Canadian sample of "Westernness, " with a special interest in concepts of authenticity and spectacle. In the present contribution, we focus on the students' response to the Stampede and on their projects, with topics ranging from animal rights to food culture, and cowboy dress codes to First Nations legacy.